Pathophysiology, Diagnosis, and Management of Papillary Thyroid Carcinoma in Thyroglossal Duct Cyst: A Review - Shaad, Shaikh Mohd; Keshavi, Mehta; Nayan, Gajghate; Sanjay, Chatterjee; Anand, Nande (Achievements and Challenges of Medicine and Medical Science Vol. 13, 2025)
Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy, but its occurrence in a thyroglossal duct cyst (TGDC) is rare, accounting for approximately 1% of cases. TGDCs result from incomplete obliteration of the thyroglossal duct during embryological development and may contain ectopic thyroid tissue. The pathogenesis of PTC within a TGDC remains unclear, with proposed mechanisms including de novo carcinogenesis or metastatic spread from primary thyroid cancer. Clinically, patients present with a painless midline neck mass, often mobile and moving with swallowing or tongue protrusion. Diagnostic evaluation includes ultrasound, fine-needle aspiration cytology (FNAC), and histopathological examination. The mainstay of treatment is the Sistrunk procedure, with thyroidectomy and lymph node dissection considered in select cases. Adjuvant therapies such as radioactive iodine and TSH suppression therapy may be utilized in high-risk patients. The prognosis is excellent with complete surgical resection. This article reviews the pathophysiology, clinical presentation, diagnostic approach, and management strategies for PTC in TGDCs, highlighting the importance of early recognition and a multidisciplinary treatment approach.